Peran Influencer Marketing dalam Meningkatkan Brand Awareness pada Generasi Z - Ibrahim, Darmawansah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study aims to analyze the role of influencer marketing in enhancing brand awareness among Generation Z. Influencer marketing is a marketing strategy that utilizes individuals with high social media influence to promote brands to their audiences. This strategy is considered effective in reaching Generation Z, who are more responsive to digital content and recommendations from influencers compared to traditional advertising. The study employs a quantitative approach using surveys for data collection. Questionnaires were distributed to Generation Z members who are active on social media and follow influencers. The results indicate that influencer marketing has a positive and significant impact on brand awareness. The presence of credible and relevant influencers helps increase brand recognition, build a positive brand image, and influence young consumers’ perceptions of the brand.